The application of the ABC attitude model to online purchasing decisions (Study on e-commerce fashion consumers in Indonesia) - Irwan Christanto Edy, Irwan Christanto Edy; Riyanto, Riyanto; Marsono, Shandi; Haryanti, Setyani Sri (Technium Social Sciences Journal, 2021)
This research aims to determine the effect of affective-cognitive direct (recursive) learning on online consumer purchasing decisions. In this study, the studied included online consumer purchasing decisions, organic stimulation of marketing on website, affective learning (emotions, preferences), cognitive learning (perception). The respondents selected in this study were the millennial generation and purchases for fashion products. Sampling method with purposive sampling method. Data collection techniques in this study using online questionnaires, which were then tested with intrusion tests that are validity and reliability tests. The results of the analysis with SEM show that the hypothesized model meets the goodness of fit criteria. The results of statistical analysis show that 1) organic stimulation of marketing on website has no effect on online consumer purchasing decisions, 2)organic stimulation of marketing on website positively affects the emotions of online consumers purchasing decisions, 3) organic stimulation of marketing on website positively affects the preference of online consumer purchasing decisions, 4) organic stimulation of marketing on website positively affects the perception of online consumer purchasing decisions, 5)affective-cognitive learning (emotion, preference and perception) has the role of effectively mediating the influence of organic stimulation of marketing in website on online consumer purchasing decisions. The findings of this study have proven that online consumer purchasing decisions in the millennial generation and for fashion products are the result of affective-cognitive direct (recursive) learning on online consumers. Based on the results of this study, the practical implication is that online businesses that rely on marketing with website media need to always pay attention to the dynamics of lifestyle, emotions, preferences, perceptions that develop among consumers and build marketing with media websites that base on the needs and learning of consumers. The study uses a new approach from the ABC attitude model, which researchers referred to as a directional (Recursive) model of affective-cognitive learning. The argument of this study is that online consumer purchasing decisions are the impact of a series of processes that are in the direction of what is perceived (affective) and further what consumers think about products promoted by e-commerce companies on the media website